2020
DOI: 10.3390/nu12123865
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Orthorexia Nervosa in Polish and Lebanese Adults and Its Relationship with Sociodemographic Variables and BMI Ranges: A Cross-Cultural Perspective

Abstract: The prevalence of orthorexia nervosa (ON) appears to be increasing, and more research into its cross-cultural aspects is required to provide culturally appropriate psychological treatment. Until now, there has been relatively little research published about ON across cultures. Therefore, the objectives of the present study were to determine: (1) the prevalence of ON in Polish and Lebanese adults and (2) the association between ON and sociodemographic variables and Body Mass Index (BMI) in two culturally differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…Sample sizes ranged from 10 to 2826 participants, with an age range of 18–92 years. Six population groups were identified; twenty‐six focused on university students, 6,24–48 12 on the general population, 49–60 10 on “health‐minded” individuals, 5,61–69 four on dietitians and health professionals, 70–73 four on people with a chronic illness, 74–77 and two on people with ED 77,78 …”
Section: Resultsmentioning
confidence: 99%
“…Sample sizes ranged from 10 to 2826 participants, with an age range of 18–92 years. Six population groups were identified; twenty‐six focused on university students, 6,24–48 12 on the general population, 49–60 10 on “health‐minded” individuals, 5,61–69 four on dietitians and health professionals, 70–73 four on people with a chronic illness, 74–77 and two on people with ED 77,78 …”
Section: Resultsmentioning
confidence: 99%
“…A German study using the DOS on 446 university students reported a prevalence of 3.3%, with a 9.0% risk of developing ON [14]. A recent study showed an orthorexia prevalence of 2.6% in Polish adults [15].…”
Section: Orthorexia Measures Of Assessmentmentioning
confidence: 99%
“…This number might be unrealistic since the validated ORTO-15 scale had low psychometric properties, which yielded a high prevalence of ON [43]. A recent study revealed an orthorexia prevalence of 8.4% in Lebanese adults using the Dusseldorf Orthorexia Scale [15]. Another study revealed that individuals from a Lebanese sample who met the criteria for ON experienced less psychological distress [44], but the literature connecting psychological distress to ON is scarce.…”
Section: Orthorexia In Lebanonmentioning
confidence: 99%
“…6%, while in Lebanese adults the prevalence rate was 8. 4% [24]. In another study, the prevalence of orthorexia nervosa among dietetics and nutrition students in Jordan was 72% with a cut-off score of 40 and 31.…”
Section: Discussionmentioning
confidence: 94%